Pengaruh Teknik Massage Counter Pressure dalam Mengurangi Rasa Sakit Persalinan pada Primipara Kala I Fase Aktif di PMB Wilayah Kerja Puskesmas Sei Langkai - Faiqah Zahra; Catur Yulinawati; Rofiqo Larasati Philip (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Pain during childbirth is a personal feeling and varies from individual to individual, including among mothers in labor. One non-pharmacological method created to overcome pain is pressure massage techniques. Pressure massage techniques can reduce pain transmitted to the spinal cord in the brain, and also provide strong pressure that can trigger the release of endorphins. This study aims to examine the effect of pressure massage techniques in reducing pain during labor in first-time pregnant women in the active phase of the first stage of labor at the PMB Work Area of ​​the Sei Langkai Community Health Center, Batam City in 2024. This type of research is Pre-Experimental with a One Group Pretest Posttest design. The number of samples taken in this study was 16 mothers in labor, with the data collection method using purposive sampling. The independent variable in this study was pressure massage, while the dependent variable was pain during labor. The instruments used in this study were SOPs and observation forms. The results showed that pain levels before and after pressure massage decreased, with an average pain level of 4.43 before and 2.25 after. This finding indicates a decrease in pain levels during childbirth by a difference of 2.18. The Wilcoxon statistical test showed a significant value with a p-value of 0.000.